DRY EYE DISEASE: CURRENT GUIDELINES AND EMERGING THERAPEUTIC STRATEGIES - Karolina Nowacka (International Journal of Innovative Technologies in Social Science, 2025)
Background: Dry eye disease (DED) is a chronic, multifactorial disorder of the ocular surface characterized by loss of tear film homeostasis, resulting in ocular symptoms and heterogeneous clinical signs. It affects both elderly and working-age populations, with increasing prevalence related to environmental exposure, digital device use, and lifestyle changes. Advances summarized in the TFOS DEWS II reports have substantially improved understanding of DED pathophysiology, highlighting the roles of tear film instability, hyperosmolarity, chronic inflammation, meibomian gland dysfunction, and neurosensory abnormalities.Methods: This narrative review analyzes current international guidelines and peer-reviewed literature published between 2015 and 2025. PubMed/MEDLINE and Google Scholar were searched using keywords related to dry eye disease, ocular surface disease, TFOS DEWS II, meibomian gland dysfunction, diagnostics, and treatment. Consensus reports, randomized controlled trials, meta-analyses, and systematic reviews were included.Results: Evidence indicates that DED is a heterogeneous condition requiring an individualized, phenotype-based diagnostic and therapeutic approach. Contemporary guidelines recommend combining symptom assessment with objective diagnostic testing to guide management. Stepwise treatment strategies emphasize patient education, environmental modification, tear supplementation, and targeted anti-inflammatory therapy. Recent advances include immunomodulatory agents, therapies for meibomian gland dysfunction, evaporation-reducing agents, neurostimulatory approaches, and biological treatments for severe or refractory disease.Conclusion: Dry eye disease remains a complex clinical challenge. Implementation of updated diagnostic criteria and stepwise, phenotype-oriented treatment strategies enables improved disease control and quality of life. Continued research into inflammatory and neurosensory mechanisms, along with development of novel therapies, is essential for further optimization of personalized DED management.